The law and economics of buyer power in EU competition policy - Doorn, Frederik van (Eleven International Publishing, 2015)
The trend of retail concentration across the European Union has raised concerns on the buyer power that retailers may have in the relation with their suppliers. Following calls that the changing nature of competition demands a change in EU competition policy, this book investigates whether there is a 'gap' in current EU competition law concerning the potential harmful effects of buyer power from an economic efficiency perspective. Using a Law and Economics approach, the book identifies the potential concerns and assesses whether they can be addressed under the existing rules. While some critic.